Manajemen Supervisi Akademik: Pendekatan Pembelajaran Mendalam Oleh Komite Pembelajaran Di Smk Negeri 2 Kendal - Candra Hermawan, Tommy; Indanarti, Indanarti; Wajiyo, Wajiyo; Soedjono (Universitas Hamzanwadi, 2026)
This study aims to analyze the management of academic supervision in the implementation of a deep learning approach conducted by the Learning Committee at SMK Negeri 2 Kendal. The research employed a qualitative case study approach. The research subjects included the principal, vice principal for curriculum and staffing, vocational and general subject teachers, members of the Learning Committee, and students. Data were collected through in-depth interviews, observations, and document analysis, while data validity was ensured through source and method triangulation. The findings indicate that academic supervision management has been implemented through the stages of planning, organizing, implementation, and evaluation. Supervision planning was collaboratively developed and aligned with the Merdeka Curriculum policy. Organizing was carried out through clear task distribution; however, limitations remain in coordination and teachers’ understanding of the deep learning concept. The implementation of academic supervision focused on instructional mentoring, classroom observation, and reflective practices, although it has not yet been conducted in a consistent and sustainable manner. Evaluation activities were conducted, but systematic follow-up actions were still limited. This study concludes that academic supervision management plays a strategic role in supporting the implementation of deep learning in vocational schools; however, it requires strengthening in terms of consistency, conceptual understanding, and sustainability of supervision practices.